Aspectos socioeconômicos da Covid-19: Evidências dos trabalhadores formais do estado do Rio de Janeiro - Fernanda De Negri; Rafael M. Galliez; Pedro Miranda; Priscila Koeller; Graziela Ferrero Zucoloto; Joana Costa; Claudio M. de Farias; Guilherme Horta Travassos; Roberto de Andrade Medronho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper aims to analyze the effects of individual socioeconomic characteristics on the mortality risk of Covid-19. Two datasets were combined to achieve this objective: the individual health records from people infected with coronavirus in the state of Rio de Janeiro, in Brazil, and the Annual Report of Social Information database (Rais), which contain diverse socioeconomic information about formal workers in the state. These datasets make it possible to estimate logistic models to assess the effect of variables such as sex, age, income, race/ethnicity, schooling, occupation, and economic activity on the risk of death from Covid-19. The results indicate that some groups of workers have more risk of dying of Covid-19 than others: workers employed in establishments in the health and public safety sectors present, respectively, a risk of dying 2.46 and 2.25 times higher than those employed in other activities. The results also show that non-white people, men, and those who work in the Metropolitan Region are more likely to die from Covid-19. On the other hand, those who have higher education are 44% less likely to die from the disease. It is essential to consider these differences in the design of prevention policies to be adopted.
Keywords: I14; I18; J01; 330; Covid-19; mortality rates; health and inequality; pandemic; public health; workers; labor market data